Pengaruh Pemanfaatan Teknologi Informasi dan Kemampuan Teknik Personal Pada Efektivitas SIA - Dwi Anggreni, Ni Made Harista; Sadha Suardikha, I Made (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p02)
The purpose of this study was to determine the effect of Utilization of Information Technology and Personal Engineering Capabilities on the Effectiveness of Accounting Information Systems. This research was conducted at the Department of Industry and Trade Denpasar City. The analysis technique used is multiple linear regression analysis techniques. The type of data used in this study is quantitative data, in the form of the results of answers by respondents expressed in the form of numbers from questionnaires that are measured using a Likert scale. The analysis shows that the use of information technology and the ability of personal techniques have a positive effect on the effectiveness of accounting information systems. Keywords: Utilization Of Information Technology; Personal Technical Ability; Effectiveness Of Accounting Information Systems.